Biofilms in ventilator-associated pneumonia. (December 2016) - Fernández-Barat, Laia; Torres, Antoni
Biofilms develop rapidly following endotracheal intubation and represent a persistent source of unnecessary pathogens in the critically ill patient. Overall, the imbalance in the lung microbiome caused by an endotracheal tube and its role in biofilm formation and in ventilator-associated pneumonia is still unclear. Although endotracheal tube–biofilm preventive measures are being tested, no outcome impact has ever been demonstrated, and therefore no approach has been clinically recommended. Nonetheless, an accurate description of the actual biofilm morphology in vivo could be useful to implement effective preventive measures. The combined use of in vitro biofilm models, in vivo animal models and clinical research is vitally important to the attainment of a comprehensive understanding of biofilms in ventilator-associated pneumonia in the near future.